CNJ’s resolution 135 and the challenge of regulating the judiciary - Ivan Candido da Silva de Franco (Brazilian Journal of Empirical Legal Studies, 2015)
The National Council of Justice (Conselho Nacional de Justiça - CNJ), created in 2004, is the administrative governing body of the Brazilian Judicial Branch (Article 103- B of the Constitution). It has the responsibility of editing rules that all the Brazilian courts must follow, except the Supreme Court (STF), and of exercising disciplinary control of judges. This article is a case study that explores a specific aspect of the CNJ’s mandate: the regulation of the disciplinary control of the judiciary. Our main goal is to understand the existing institutional dynamics and to understand how this issue was undertaken throughout the Council’s history: what kind of resistance was encountered in this process and which actors were involved in the ongoing debates. The institutional path, which begins with a fragile regulation from the CNJ’s Internal Regiment, and then gives rise to the first resolution of disciplinary matters, is described and analyzed.  Ultimately, this path results in the current regulation, the Resolution 135/2011, which promotes significant changes in the disciplinary rules and, because of that a Direct Action of Unconstitutionality (Ação Direta de Inconstitucionalidade -ADI) challenged it before the Brazilian Supreme Court.